2019
DOI: 10.1002/adom.201801229
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Visible Light Energy Transfer to Ultrathin Semiconductor Films Enabled by Dispersion Control

Abstract: dielectric and semiconductor [2] nanostructures. In addition, to extend absorption over a broader range of the solar spectrum, multiple semiconducting layers with different absorption bands have been used to create multijunction solar cells. [11,12] Despite such efforts, the high efficiency thin-film semiconductor absorber is still a topic of active research. The classical Yablonovitch limit [13] of maximum achievable absorption, which is based on geometrical optics, does not apply to ultrathin semiconductor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Moreover, because the Brewster mode mostly exists in transvers magnetic (TM) polarization only, the absorption of transverse electric (TE) polarization is much lower than that of TM polarization. Some research groups have addressed these problems by using a spacer below the highly absorbing layer 2325 , metal-semiconductor-metal cavity structure 26 , metamaterials 2729 , lossy magnetic mirrors 17 , and cavity tuning for aesthetic purpose 30,31 . However, so far, it remains a challenge to make incident-angle and polarization-independent optical absorbers that cover a wide range of wavelengths (over the whole visible range) without using complex fabrication procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because the Brewster mode mostly exists in transvers magnetic (TM) polarization only, the absorption of transverse electric (TE) polarization is much lower than that of TM polarization. Some research groups have addressed these problems by using a spacer below the highly absorbing layer 2325 , metal-semiconductor-metal cavity structure 26 , metamaterials 2729 , lossy magnetic mirrors 17 , and cavity tuning for aesthetic purpose 30,31 . However, so far, it remains a challenge to make incident-angle and polarization-independent optical absorbers that cover a wide range of wavelengths (over the whole visible range) without using complex fabrication procedures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the maximum absorptivity of ~82.57% appears at 550 nm, and the average absorption remains above around 65% over the visible regime for a typical design of 10 nm Ge/100 nm silver (Ag), as presented in Figure 1b(i). To further enhance the optical absorption, one widely used design is the semiconductor-dielectric-metallic mirror structure, in which the top semiconductor film is required to exhibit an unusual type of material dispersion [2,32,34]. Although an effective medium design using two absorbing films [34] and controlling the semiconductor's polycrystallinity [32] was proposed to match the ideal optical complex refractive index, the near-unity absorption band still cannot cover the entire visible range, and the fabrication costs were also increased.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was found that strong interference effects could be excited in an ultrathin absorbing semiconductor film coated on a metallic substrate, leading to strong absorption with a broad bandwidth at the resonant wavelength [30]. Although many broadband absorber designs have been proposed by utilizing ultrathin semiconductor films, the near-unity absorption characteristic cannot cover the whole visible range [2,31,32]. Therefore, how to achieve more efficient absorption over a wider spectral range with simpler planar thin-film structures still remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring the film nanostructure [5,22] enables tuning its effective optical dispersion in a broad range. This is useful to meet the requirements for an optimal light harvesting [23] in Bi nanostructured materials, in particular for photocatalytic systems based on near-percolation Bi nanostructures [24][25].…”
Section: Discussionmentioning
confidence: 99%